IDENTIFIKASI TUMBUHAN BERMANFAAT DALAM KEHIDUPAN MASYARAKAT SENTANI BARAT SEBAGAI SUMBER BELAJAR IPA PADA MATERI KEANEKARAGAMAN TUMBUHAN SISWA KELAS VII SMP NEGERI SATU ATAP SABRON SARI - Henny Marlina; Tiurlina Siregar (Program Magister Pendidikan IPA, Program Pascasarjana Universitas Cenderawasih, 2018)
Abstract Research on Identification of Beneficial Plant In West Sentani Community Life as a Learning Resource Materials Science On Plant Diversity Seventh Grade Students of SMP One Roof Sabron sari. This study aims to: 1). To find out how to use the environment as a learning resource; 2). To identify herbs used in the West Sentani community life; 3). To determine student interest in learning to identify plants around the school: 4). To determine the students' skills in identification. This research is a qualitative research. Methods or techniques of data collection conducted a descriptive one that is interactive. The results showed that: 1). By way of using the environment as a learning resource can provide a real experience, direct and attractive to students, through a collection of plants were obtained. 2). By way of directly observing and comparing the characteristics of plants that used sentani western societies are able to decide 4 Division, Grades 5, 20 Nations, 24 tribes, 29 Marga, and 30 types of plants. 3). The increased interest of student learning 75.11% by using the environment as a learning resource IPA. 4). 67.16% of students skilled in identifying plants scientifically and correctly. The benefits that can be taken by students is that students can take advantage of the environment as a learning resource, it can identify the types of plants are found, learning and student skills in the use of the environment as a learning resource in both categories.Keywords: Identification of Plants, Plant helpful and Junior High School Students One RoofSabron Sari class VII